In situ scanning tunneling microscopy study of bipyridine adsorption at semi-metallic Sb(111) plane - Georg Gorbatovski; Ove Oll; Heili Kasuk; Piret Pikma; Enn Lust (Electrochemistry Communications, 2019)
The adsorption characteristics and organic adlayer formation properties of bipyridine molecules at semi-metallic Sb(111) electrodes in an aqueous electrolyte solution are studied by means of in situ scanning tunnelling microscopy (STM), cyclic voltammetry and electrochemical impedance spectroscopy. The capacitance–potential response shows a small capacitance hump for 4,4′-bipyridine (BP) adsorption at the Sb(111) interface, the position of which is slightly dependent on the electrolyte pH. No such capacitance vs. potential curve feature was observed for the adsorption of 2,2′-BP at Sb(111). STM measurements show a clean initial surface structure for the 4,4′-BP system and a higher level of noise interference in the case of the 2,2′-BP│Sb(111) system. The atomic resolution of the Sb(111) structure can be measured for both 2,2′-BP and 4,4′-BP additives and the formation of adsorbed molecular rows can be observed for the 4,4′-BP additive at the Sb(111) surface. The surface coverage of the molecules and the gaps between them suggest that 4,4′-BP is adsorbed in bi-protonated form with solvated anions stabilizing the adlayer structure. The reduction of BP molecules starts negative polarization and is significantly both pH- and potential-dependent. The formation of non-structured deposits is seen as a result of this process, which is deemed to be irreversible. Keywords: Self-assembled monolayer, Specific adsorption, Bipyridine, Sb(111), In situ STM